Self-Acces in Digital Literacy: Evaluating the Quality of Information and Reliability of Sources in Writing Academic Essay - Abdul Haliq; Zamzani Zamzani; Pangesti Wiedarti; Akhiruddin Akhiruddin (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. Digital literacy skills have a positive impact on managing academic tasks, including writing academic essays. This study aims to describe the reliability of references and the quality of information content in student academic essays. This research focuses on students' digital literacy activities in accessing valid reference sources and to produce digital content that has quality information content. This research was conducted on 30 students who participated in face-to-face and independent learning and independent learning in writing academic essays. Students' academic essays were analyzed to obtain data on the reliability of references and the quality of information content. Student responses were obtained from questionnaires and interviews to gather data on the reasons for selecting references. Data analysis shows that students still use blogs, Wikipedia, and online newspapers as references on the grounds of their relevance to the writing being developed. The results of the analysis of the information content of student academic essays show that students can make academic essays that have quality information content worthy of being disseminated in the digital world.  Keywords:   References, Academic Essays, Reliability, Information Content.